Gur-Emir Mausoleum is a Masterpiece of Timurid Architecture - Makhmudova M.T. (Periodica Journal, 2023)
The article provides information about the mausoleum of Amir Temur in Samarkand, the history of its creation, planning and compositional solutions, mausoleum structures, decoration of facades and interiors, restoration of the monument, its influence on the construction of similar buildings in other parts of the world
Keywords: Mausoleum; Amir Temur; architecture; khanaka